2005
DOI: 10.1637/7375-05040r.1
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Infection of Turkeys with Listeria monocytogenes Scott A

Abstract: The pathogenesis of L. monocytogenes strain Scott A was studied by challenging day-old male turkey poults by air sac inoculation with tryptose phosphate broth containing 10(0) cfu (control), 10(4), 10(5), and 10(6) cfu (low challenge), or 10(7) and 10(8) cfu (high challenge) of the Scott A (serotype 4b) strain of L. monocytogenes. Mortality at 2 wk postinfection (PI) ranged from 25% for low challenge to 100% for high challenge (P= 0.0001). Gross and histopathological lesions were observed in heart, liver, sple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…There is greater evidence for potential systemic Listeria infection in other avian species, such as turkeys. Huff et al ( 69 ) demonstrated in young turkey poults inoculated with a high or low dose of L. monocytogenes Scott A in the air sac that the high dosed birds reached 100% mortalities in 2 weeks, and the Listeria challenge strain could be isolated from the liver, pericardium, brain, both knee joints, suggesting that L. monocytogenes Scott A could be invasive through the respiratory system of susceptible turkey poults. In a follow-up challenge study comparing oral or oculonasal routes, Huff et al ( 70 ) demonstrated that the oculonasal route led to greater mortalities and lower body weights than orally challenged birds.…”
Section: Potential For Listeric Infections In Poultrymentioning
confidence: 99%
“…There is greater evidence for potential systemic Listeria infection in other avian species, such as turkeys. Huff et al ( 69 ) demonstrated in young turkey poults inoculated with a high or low dose of L. monocytogenes Scott A in the air sac that the high dosed birds reached 100% mortalities in 2 weeks, and the Listeria challenge strain could be isolated from the liver, pericardium, brain, both knee joints, suggesting that L. monocytogenes Scott A could be invasive through the respiratory system of susceptible turkey poults. In a follow-up challenge study comparing oral or oculonasal routes, Huff et al ( 70 ) demonstrated that the oculonasal route led to greater mortalities and lower body weights than orally challenged birds.…”
Section: Potential For Listeric Infections In Poultrymentioning
confidence: 99%
“…It is significant that L. monocytogenes can colonize the murine gall bladder following oral or intravenous administration (Hardy et al, 2004; Bron et al, 2006). It can also be isolated from the gall bladder in infected guinea pigs (Jensen et al, 2008) and turkeys (Huff et al, 2005), but not in infected sheep (Zundel and Bernard, 2006). There is also evidence suggesting that L. monocytogenes may be a rare cause of human cholecystitis (infection of the gall bladder) (Allerberger et al, 1989; Descy et al, 2012; Bruminhent et al, 2013).…”
Section: Potential For Faecal or Gall Bladder Carriagementioning
confidence: 99%
“…Under normal physiological conditions, the bile concentration in the human gut is between 0.005 and 2% (Dawson, 1998 ). Strikingly, L. monocytogenes is able to grow in gall bladders (Hardy et al, 2004 , 2006 ; Huff et al, 2005 ; Jensen et al, 2008 ; Dowd et al, 2011 ), where bile is concentrated at neutral pH. However, once bile is released into the duodenum postprandially, it becomes active in this low pH environment (Dowd et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%